Commodity Outlook 2003: U.S. Agronomic Crop Market - Tim Hewitt (EDIS)
The 2003 outlook for agronomic crops has been highlighted by changes resulting from the 2002 U.S. Farm Bill: smaller supplies and increased prices. Also, many changes have been implemented in commodity programs. This is EDIS document FE372, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published February 2003.